VISTA functions as a protective immune checkpoint in indirect acute respiratory distress syndrome by modulating systemic and compartmentalized inflammation - Baoji Hu; Baoji Hu; Baoji Hu; Chun-Shiang Chung; Chyna Gray; Yaping Chen; Jihong Jiang; Jihong Jiang; Jianrong Guo; Jianrong Guo; Alfred Ayala (Frontiers in Immunology)
BackgroundIndirect acute respiratory distress syndrome (iARDS) is a life-threatening inflammatory lung injury often triggered by extrapulmonary insults. Although immune checkpoints are critical regulators of inflammation, the role of V-domain Ig suppressor of T-cell activation (VISTA) in iARDS remains unexplored.MethodsUsing a murine model of iARDS, we compared outcomes in VISTA knockout (VISTA−/−) and wild-type mice. Disease severity was assessed through lung injury scoring, survival analysis, and cytokine/chemokine profiling in plasma, lung tissue, and peritoneal fluid. The therapeutic potential of VISTA was evaluated using an anti-VISTA antibody (13F3).ResultsVISTA−/− mice exhibited exacerbated lung injury, reduced survival, and elevated systemic levels of interleukin (IL)-6, IL-10, MIP-2, and KC compared to wild-type controls. While cytokine levels in lung tissue remained stable, peritoneal fluid mediators were dysregulated in VISTA−/− mice, highlighting compartment-specific inflammatory regulation. Treatment with 13F3 reduced VISTA expression on myeloid and structural cells (monocytes, neutrophils, macrophages, epithelium, endothelium) and partially modulated cytokine/chemokine profiles across compartments.ConclusionOur findings establish VISTA as a protective immune checkpoint in iARDS that restrains systemic hyperinflammation and organ damage. Although antibody-mediated VISTA targeting altered inflammatory pathways, its incomplete efficacy suggests complex, multifactorial mechanisms at play. These results position VISTA as a novel therapeutic target for iARDS and warrant further exploration of timed immunomodulatory strategies to harness its protective effects.